AKUNTABILITAS SELEKSI TERBUKA JABATAN PIMPINAN TINGGI PRATAMA SEKRETARIS DAERAH KABUPATEN BLORA - M. Aminudin; Sumartono Sumartono; Tjahjanulin Domai (Department of Public Administration, Universitas Negeri Surabaya, 2017)
Mechanism more relevant to fill structural positions on the value of accountability and meritocracy is open selection. Law No. 5 of 2014 concerning the State Civil Apparatus require the completion of High vacant leadership positions using the system, therefore Blora District Government to implement an open selection to fill leadership positions High Primary Regional Secretary. This study aimed to analyze the elements of procedural accountability of leadership positions open selection of Blora District Secretary. The approach used is qualitative descriptive analysis. Methods of data collection using interviews, documentation, correspondence and normative literature. The results showed step by step filling the position through an open selection since the formation of the selection committee, the establishment of standards of competence, the selection of competence, search the track record, the interview, the announcement of the selection results even coordination with the Governor and the Commission ASN has been accountable to fulfill the norms of legislation, namely Law No. 5 of 2014 concerning the State Civil Apparatus and PERMENPAN RB No. 13 Year 2014 regarding the Procedures Completion of High Leadership Position Openly in Environment Government Agencies.